The gap remains: The challenge of translating research into policies for the health care of people and communities - Barría P., Mauricio (Investigación y Educación en Enfermería, 2017)
In health sciences, day-to-day a large amount of research is accumulated in different settings and contexts, which serve as the substrate for decisionmaking at the individual and collective clinical level. Nevertheless, strategies persist to modify the clinical practice based more on beliefs than on scientific evidence. In addition, although research evidence is generated at a growing rhythm, the clinical practice to reflect this evidence has been delayed.(1) According to the evidence-based practice model, the gold standard that supports the best recommendation for prevention and therapeutic interventions is constituted by the randomized controlled trial. Although it is also recognized that this design does not manage to establish if the treatment context influences upon the trial results or how an intervention achieves its effects beyond the study scenario. Thus, the difficulty of translating research findings suggests that an intervention that has demonstrated effectiveness needs to address the context for implementation. How to cite this article: Barría RM. The gap remains: The challenge of translating research into policies for the health care of people and communities. Invest. Educ. Enferm. 2017; 35(2):129-130.